2023
DOI: 10.1007/s12325-023-02468-3
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast Use in Severe Psoriasis: Real-World Data from Central and Eastern Europe

Abstract: Introduction The broad and sustained efficacy of apremilast for psoriasis has been demonstrated in randomized and real-world observational studies. Data from Central and Eastern Europe (CEE) are lacking. Moreover, apremilast use in this region is limited by country-specific reimbursement criteria. This is the first study to report data on the real-world use of apremilast in the region. Methods APPRECIATE (NCT02740218) was an observational, retrospective, cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It is widely reported that patient-perceived burden can be unrelated to the severity and extent of psoriasis [ 7 , 8 , 32 ]. Previous real-world studies with apremilast have reported similarly high disease burden among patients with moderate skin involvement and clinically relevant improvements following apremilast treatment [ 17 , 18 , 21 , 23 , 36 , 37 ]. LAPIS-PSO, a real-world study focused on QoL, reported that patients with moderate-to-severe plaque psoriasis benefited from apremilast treatment up to approximately 13 months of observation [ 27 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is widely reported that patient-perceived burden can be unrelated to the severity and extent of psoriasis [ 7 , 8 , 32 ]. Previous real-world studies with apremilast have reported similarly high disease burden among patients with moderate skin involvement and clinically relevant improvements following apremilast treatment [ 17 , 18 , 21 , 23 , 36 , 37 ]. LAPIS-PSO, a real-world study focused on QoL, reported that patients with moderate-to-severe plaque psoriasis benefited from apremilast treatment up to approximately 13 months of observation [ 27 ].…”
Section: Discussionmentioning
confidence: 98%
“…Placebo-controlled randomized clinical trials demonstrated the efficacy and tolerability of apremilast in patients with moderate-to-severe plaque psoriasis previously treated with or naïve to biologics [ 14 16 ]. The retrospective, cross-sectional APPRECIATE study has reported the characteristics of patients with psoriasis treated with apremilast in routine clinical practice across nine European countries, and treatment needs and outcomes from the perspectives of both physicians and patients [ 17 , 18 ]. APPRECIATE used validated disease severity scores, including PASI and BSA, and patient-reported outcomes such as the Dermatology Life Quality Index (DLQI), the 9-item Treatment Satisfaction Questionnaire for Medication (TSQM-9), and the Patient Benefit Index (PBI).…”
Section: Introductionmentioning
confidence: 99%